The impact of change management on the organizational performance of higher education institutions (Applied to Imam Muhammad bin Saud Islamic University) - Alotaibi, Taghreed Mater (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to know the effect of change management on organizational performance at Imam Muhammad bin Saud Islamic University from the point of view of the university’s faculty members. The researcher used the descriptive analytical approach, to achieve the objectives of the research. A stratified amount of (96) from the university faculty, and the (R) program was used to analyze the data. The results of the study showed that the tool’s general obtained a total average (4.21 out of 5 ) that refers, to a (high) degree, and on the level of the two axes; The organizational change obtained a total average of 3.7 out of 5that refers to a (medium) degree, while the organizational performance got a total average of 3.2 out of 5), i.e., with a rating of (average).. The results also showed a positive, statistically significant relationship between change management and organizational performance, and the correlation coefficient was 0.54 It reflects a strength (medium), and based on the results, the researcher recommended the necessity of the Accreditation and Quality Commission to follow up on the global developments taking place in university performance, and to re-design the university performance standards at the Ministry of Education in accordance with modern requirements and to benefit from foreign experiences to improve the quality and quality of university performance with the application of standards by higher education institutions, In addition to suggestions for complementary studies on the subject.
Keywords: relationship; change management; organizational performance; university performance; Muhammad bin Saud Islamic University